PENGATURAN DAN PEMBINAAN PEDAGANG KAKI LIMA MENURUT PERATURAN DAERAH KOTA SEMARANG NOMOR 11 TAHUN 2000 DI KAWASAN SIMPANG LIMA KOTA SEMARANG - Khaerina Hidayah; Aloysius Rengga (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
Street vendors often become a major problem in a big city, including Semarang city. Semarang city is one of the metropolis city, a magnet for economically weak society, including street vendors, which are small businesses in the informal sector. Semarang city government through regional regulation no. 11 year 2000 about Regulation and Development of Street Vendors launched a program to regulate and develop street vendors. One of the concentrated growth area of street vendors in Semarang is on Simpang Lima. Simpang Lima street vending area is a street vending area example but there are still some problems in the implementation. These problems are the considerably huge amount of illegal street vendors, the imbalance of shelters for legal street vendors, and street vendors’ undisciplined behaviors of vending time and vending place tidiness. This research uses descriptive qualitative research method and the data collection technique is by thorough interview, field observation, and documentation. In this research, the author will describe about regulation and development of street vendors according to Regional Regulation no. 11 year 2000 and the problems of its implementation. In studying the regulation and development constraints used Mazmanian and Sabatier theory that there are three dimensions that influence the successful implementation of which is the problems’ characteristics, the policies’ characteristics, and the policies’ environment. The result of research, regulation and development of street vendors implementation is not going well yet because of many obstacles caused by the target group and the lack of resolute and decisive actions by the implementing enforcement authorities. These obstacles include lack of land to accommodate the increasing number of street vendors who continue to grow, the Rule of Law principle that less is held by implementing policies, the target group is stubborn and implementing policies that are less strict in implementing the policy. No significant thing done by the Government, they seemed indifferent to all the problems that occur due regard street vendors in the area of Simpang Lima has been orderly and organized.